Application of indocyanine green fluorescence for precision sublobar resection. Issue 4 (7th February 2019) - Zhang, Chao; Lin, Huan; Fu, Rui; Zhang, Tao; Nie, Qiang; Dong, Song; Yang, Xue‐Ning; Wu, Yi‐Long; Zhong, Wen‐Zhao
Abstract : Background: Increasing identification of small pulmonary nodules promotes sublobar resection, but localization and surgical margins of non‐palpable pulmonary nodules through sublobar resection are challenging. Our aim was explicate the feasibility of applying indocyanine green (ICG) fluorescence to localized nodules, and to carry out surgical resection. Methods: A total of 46 patients with subpleural pulmonary nodules <3 cm were enrolled, including 35 for wedge resection and 11 for segmentectomy. For wedge resection, patients underwent computed tomography‐guided percutaneous injection of ICG preoperatively. Wedge resection was carried out after confirmation of the fluorescence using fluoroscopy. For segmentectomy, ICG was injected through the peripheral vein during surgery and resection of the segmental plain was carried out. Detailed measurements were taken and information was collected for the whole procedure. Results: A total of 33 out of 35 patients underwent successful wedge resection using ICG fluorescence. Segmentectomy was successfully carried out for all 11 patients who underwent the procedure. For two patiens, the nodules failed to be localized with unclear fluorescence, and one patient with an undetected nodule was altered to perform lobectomy. For wedge resection, the mean tumor size and depth from the pleural surface were 7.8 ± 0.5 mm and 10.5 ± 1.6 mm, respectively. The median time taken for preoperative computed tomography‐guided percutaneous injection was 28 min (range 18–40 min), and 25 min (range 16–30 min) for wedge resection. For segmentectomy, the ICG fluorescence occurred 14 s after injecting ICG through the peripheral vein, and the median duration was 15 min. All surgical margins were negative based on pathological evaluation. Conclusions: The implementation of ICG fluorescence could provide surgeons carrying out precision sublobar resection with a time‐saving surgical technique with less unnecessary intraoperative damage.